ENERGY MANAGEMENT IN MICROPROCESSOR-DRIVEN CIRCUIT DESIGN USING SLEEP MODES - Igrec, Dalibor; Hebar, Jože; Chowdhury, Amor (Journal of Energy Technology, 2025)
The article explores the important significance of sleep mode in the design of microprocessorcentric electronic devices, emphasising energy efficiency, device longevity and environmental sustainability. Sleep mode enables devices to enter low-power states during periods of inactivity, conserving energy and extending battery life. Various levels of sleep modes are examined, ranging from light to deep sleep, each with unique power savings and system responsiveness advantages.1 The article also presents a case study involving an electronic circuit controlling sensors, actuators, LTE, WiFi and a geolocation module, where sleep mode is utilised to optimise power consumption. The system operates at varying activity levels, and the employment of sleep modes such as light sleep, deep sleep and hibernation, results in energy savings exceeding 70%. Light Sleep offers rapid responsiveness with moderate power savings, while Deep Sleep and Hibernate Mode maximise energy efficiency but require longer wake-up times. The design approach emphasises the importance of managing the system components carefully, and transitioning between different power modes to ensure an optimal balance between energy conservation and performance. Finally, the article discusses the broader environmental impact of sleep mode, noting its contribution to reducing devices' energy demands and carbon footprints. By integrating effective sleep mode strategies, designers can create energy-efficient systems that meet both consumer expectations and environmental responsibilities, supporting sustainability efforts in electronic device design.
Keywords: Energy Management; Sleep Mode; Microprocessor; lectronic Circuit Design; Efficiency